Analysis of inclusive growth in ASEAN countries - Firdha Aksari Anindyntha (Optimum: Jurnal Ekonomi dan Pembangunan, 2023)
There are 17 goals to achieve sustainable development in Sustainable Development Goals (SDGs) adopted by the United Nations. One of SDG that promote inclusive and sustainable economic growth is SDG number 8. Sustainable economic growth seeks to achieve goals that support the process of economic development. Inclusive growth is sought to support the process of economic growth and economic development to prevent future generations from suffering depletion of resources.  The effort to achieve inclusive growth in line with the Sustainable Development Goals (SDGs). ASEAN was formed as an integration of any counties as a result of globalization,. The integrated economies of ASEAN countries form economic liberalization, giving rise to economic openness. The manifestation of economic openness is trade openness and financial openness.  The panel regression method is used to see the effect of economic openness and macroeconomic variables on economic growth as a proxy for inclusive growth. The results found that inflation and unemployment as macroeconomic variables had a significant negative effect on economic growth. It means to achieve the inclusive growth; the ASEAN countries should keep the inflation stable and low unemployment rate.